Exploring Strategic Entrepreneurship Research: A Comprehensive Decadal Bibliometric Analysis - Sundar, S.; Gurupandi, M. (International Review of Management and Marketing, 2024)
Strategic entrepreneurship indeed plays a crucial role in contemporary business environments. It integrates entrepreneurial actions with strategic management practices to navigate complexities and achieve long-term goals effectively. With an emphasis on trend analysis, collaborative mapping, and future objectives for the subject, bibliometric analysis of strategic entrepreneurship research is attempted to be done comprehensively in this work. The research aims to offer insights into strategic entrepreneurship literature's development and current status by utilizing data from the Scopus database spanning a decade of 2014 – 2024 with the 694 documents. The methodology involves collecting and analyzing data from Scopus using tools like Bibliometrix for data extraction and R-Studio for statistical analysis. VOSviewer is employed for visualizing co-authorship networks, keyword co-occurrences, and bibliographic couplings. The study filters publications using specific criteria related to strategic entrepreneurship, ensuring a focused dataset for analysis. Key metrics such as publication growth rates, international collaboration percentages, citation trends, and keyword frequencies are quantitatively analyzed to uncover patterns and relationships within the literature. By utilizing advanced bibliometric techniques, it provides a detailed visualization of the research landscape, highlighting emerging trends and identifying gaps for future exploration. The emphasis on international collaboration and the identification of influential authors, journals, and institutions offer novel perspectives on the dynamics of strategic entrepreneurship research.